AdipoRon, a new therapeutic prospect for Duchenne muscular dystrophy. Issue 2 (21st January 2020) - Abou‐Samra, Michel; Selvais, Camille M.; Boursereau, Raphael; Lecompte, Sophie; Noel, Laurence; Brichard, Sonia M.
Abstract: Background: Adiponectin (ApN) is a hormone known to exhibit insulin‐sensitizing, fat‐burning, and anti‐inflammatory properties in several tissues, including the skeletal muscle. Duchenne muscular dystrophy (DMD) is a devastating disease characterized by dystrophin deficiency with subsequent chronic inflammation, myofiber necrosis, and impaired regeneration. Previously, we showed that transgenic up‐regulation of ApN could significantly attenuate the dystrophic phenotype in mdx mice (model of DMD). Recently, an orally active ApN receptor agonist, AdipoRon, has been identified. This synthetic small molecule has the advantage of being more easily produced and administrable than ApN. The aim of this study was to investigate the potential effects of AdipoRon on the dystrophic muscle. Methods: Four‐week‐old mdx mice ( n = 6–9 per group) were orally treated with AdipoRon (mdx‐AR) for 8 weeks and compared with untreated (mdx) mice and to control (wild‐type) mice. In vivo functional tests were carried out to measure the global force and endurance of mice. Ex vivo biochemical and molecular analyses were performed to evaluate the pathophysiology of the skeletal muscle. Finally, in vitro tests were conducted on primary cultures of healthy and DMD human myotubes. Results: AdipoRon treatment mitigated oxidative stress (−30% to 45% for 4‐hydroxy‐2‐nonenal and peroxiredoxin 3, P < 0.0001) as well as inflammation in muscles of mdx mice (−35% to 65% for interleukin 1 beta, tumour necrosis factor alpha, and cluster of differentiation 68, a macrophage maker, P < 0.0001) while increasing the anti‐inflammatory cytokine, interleukin 10 ( 5‐fold, P < 0.0001). AdipoRon also improved the myogenic programme as assessed by a 2‐fold rise in markers of muscle proliferation and differentiation ( P < 0.01 or less vs. untreated mdx). Plasma lactate dehydrogenase and creatine kinase were reduced by 30–40% in mdx‐AR mice, reflecting less sarcolemmal damage ( P < 0.0001). When compared with untreated mdx mice, mdx‐AR mice exhibited enhanced physical performance with an increase in both muscle force and endurance and a striking restoration of the running capacity during eccentric exercise. AdipoRon mainly acted through ApN receptor 1 by increasing AMP‐activated protein kinase signalling, which led to repression of nuclear factor‐kappa B, up‐regulation of utrophin (a dystrophin analogue), and a switch towards an oxidative and more resistant fibre phenotype. The effects of AdipoRon were then recapitulated in human DMD myotubes. Conclusions: These results demonstrate that AdipoRon exerts several beneficial effects on the dystrophic muscle. This molecule could offer promising therapeutic prospect for managing DMD or other muscle and inflammatory disorders.